Answer:
![y=3x^(2) -x+5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p1a648p6qouw9odxuvajgssvq2lar0tj30.png)
Explanation:
The general form of a parabola is
![y=ax^(2) +bx+c](https://img.qammunity.org/2020/formulas/mathematics/high-school/169cnr250167ro0kovoll9jl7jswracc4w.png)
Now, we have three points, where each of them gives values for (x,y). We can use them to create a system of three equations with three unknown variables
![5=c\\7=a(1)^(2) +b(1)+c\\19=a(-2)^(2) +b(-2)+c](https://img.qammunity.org/2020/formulas/mathematics/middle-school/87ea6wanvvpu72cxf65d6y2uxiy1cqf6fo.png)
Then, we replace the value of
in the second and third equation to find create an equation with only two variables
![7=a+b+5\\19=4a-2b+5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2pgwlmoje3a0e59m0a3tnn3t2cszs8xwae.png)
![2=a+b\\14=4a-2b](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8nz5oo2eg5h1b7g48zzfbtqq73l59oc8wj.png)
Then, we multiply the first equation by 2, and sum both equations
![4=2a+2b\\14=4a-2b](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xmfsjunwlmngap29uv6tfifbvhw875b2z1.png)
![18=6a\\a=(18)/(6)\\ a=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iuug8khyvb45pwlvrf9kzau16r2shpooem.png)
Finally, we use this value to find
![b](https://img.qammunity.org/2020/formulas/mathematics/high-school/qj3i2zl0ag513n6zrlb3b1h0k0lf8u4ezr.png)
![2=a+b\\2=3+b\\b=2-3\\b=-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8ya38rnzbn9w8xpw4pvmbbh20vtz8elgt9.png)
Therefore, the equation of the parabola is
![y=ax^(2) +bx+c\\y=3x^(2) -x+5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k8ygqpme6obzqo2pbgv985yhu8vq7j3e9t.png)